2012
DOI: 10.1371/journal.pone.0044959
|View full text |Cite
|
Sign up to set email alerts
|

Clues to Occult Cancer in Patients with Ischemic Stroke

Abstract: BackgroundWe hypothesized that hidden malignancy could be detected in patients with cryptogenic stroke without active cancer when they showed the distinctive characteristics of cancer-related stroke.Methods and FindingsAmong 2,562 consecutive patients with acute ischemic stroke, patients with cryptogenic stroke were analyzed and categorized into two groups according to the presence of active cancer: cryptogenic stroke with active cancer (cancer-related stroke, CA-stroke) group and without active cancer (CR-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 25 publications
(26 reference statements)
3
91
1
5
Order By: Relevance
“…In a recent analysis of patients with cryptogenic stroke, patients with active cancer were present (71 of 348 patients; 20%) and had distinctive D-dimer levels (a marker of coagulopathy, >20× higher than those without cancer) and infarct patterns (multiple lesions in multiple vascular territories). 60 Interestingly, in this study, among 10 patients who showed such characteristics but no known cancer, workup for hidden malignancy reveled occult cancer in all patients (Figure 4). Therefore, patients who present with characteristic symptoms and infarct patterns, and no other apparent explanation for their index stroke, D-dimer level and screening for hidden malignancy (serological or radiological tests) should be considered.…”
Section: Workup For Cancer-related Coagulopathymentioning
confidence: 50%
“…In a recent analysis of patients with cryptogenic stroke, patients with active cancer were present (71 of 348 patients; 20%) and had distinctive D-dimer levels (a marker of coagulopathy, >20× higher than those without cancer) and infarct patterns (multiple lesions in multiple vascular territories). 60 Interestingly, in this study, among 10 patients who showed such characteristics but no known cancer, workup for hidden malignancy reveled occult cancer in all patients (Figure 4). Therefore, patients who present with characteristic symptoms and infarct patterns, and no other apparent explanation for their index stroke, D-dimer level and screening for hidden malignancy (serological or radiological tests) should be considered.…”
Section: Workup For Cancer-related Coagulopathymentioning
confidence: 50%
“…Clinical presentation of CVD in cancer patients is common: 14.6% of such patients have pathologic evidence of CVD, and 7.4% show clinical symptoms [5] . Although current therapeutic strategies improve the survival rate and extend the lifetime of cancer patients, increased risk of ischemic stroke is frequently observed in the same individuals [6] . Therefore, exploring the therapeutic strategies for recent ischemic stroke in cancer patients is a serious challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Kim et al found a 20.4% of patients with cryptogenic stroke had active cancer at the time of stroke. The common sites were lung, lymphoma, hepatobiliary and gastrointestinal [17,18]. Clues to OM in these patients include high D-dimer levels (odd ratio 1.11 per 1 µg/mL increase) and multiple ischemic lesions in multiple vascular territories as shown by two retrospective studies [17].…”
Section: Cryptogenic Stroke With Signs or Symptoms Suggestive Of An Omentioning
confidence: 92%
“…The common sites were lung, lymphoma, hepatobiliary and gastrointestinal [17,18]. Clues to OM in these patients include high D-dimer levels (odd ratio 1.11 per 1 µg/mL increase) and multiple ischemic lesions in multiple vascular territories as shown by two retrospective studies [17]. Therefore, patients with acute ischemic stroke should be encouraged to undergo age appropriate screening for cancer.…”
Section: Cryptogenic Stroke With Signs or Symptoms Suggestive Of An Omentioning
confidence: 99%
See 1 more Smart Citation